Time-Domain Analysis for Current Control in Single-Phase Distribution Networks Using SMES Devices With PWM-CSCs (2018)
This paper presents a time-domain analysis for current control in single-phase distribution networks using superconducting magnetic energy storage devices connected through pulse-width modulated current source converters. The control law is designed through a combination of the classical feedback linearization control technique and the intrinsic Hamiltonian structure of the system. The stability analysis of the dynamical system is done through the temporal solution of the differential equations that represent the closed-loop dynamical system. The proposed controller does not require of the single phase-phase locked loop which does a strategy very attractive due to that avoids all the problems that these elements contain, increase the reliability of the system and reducing implementation costs. The effectiveness and the robustness of the proposed current control methodology are tested in a low-voltage single-phase distribution network. All simulation scenarios are conducted in MATLAB/ODE environment under time-domain reference frame. © 2019, © 2019 Taylor & Francis Group, LLC.